Fissurforseglinger som kariesprofylakse. En kvalitativ undersøkelse av felles retningslinjer for indikasjon og bruk ved seks klinikker i Nordland og Troms - Østensen, Joakim; Karlsen, Tone-Lise; Frøysa, Lene (UiT Norges arktiske universitet, 2015)
The aim of this study was to investigate the use of and indications for sealants with different operators and then to compare the findings with the evidence-based literature. We wished to look at whether what is practised in the Public Dental Service (PDS) corresponded with what is described in the literature, and whether there are any guidelines. We undertook a qualitative study combined with a literature review. Six heads of clinics employed in the PDS were interviewed. The literature was searched to find the current knowledge base. There was broad consensus among those interviewed about fissure sealing molars in high risk patients, even in the absence of common national guidelines. Two of the interviewees stated that there existed clear guidelines for application of sealants, while two others expressed a wish that sealants be included in a regular prophylaxis program. None of the clinics systematically updated evidence for the use of sealants. The literature shows that fissure sealing is an effective prophylactic method in high risk patients. Sealants are an effective measure to reduce caries in individuals with high caries activity. In a low caries population, we know little about the cost effectiveness of this strategy. The use of sealants varies between different operators and is not necessarily consistent with the evidence-based literature. No national guidelines for the use of and indication for sealants exist in Norway to date.